On the Time Periodic Free Boundary Associated to Some Nonlinear Parabolic Equations. (2nd November 2010) - Badii, M.; Díaz, J. I.
Abstract : We give sufficient conditions, being also necessary in many cases, for the existence of a periodic free boundary generated as the boundary of the support of the periodic solution of a general class of nonlinear parabolic equations. We show some qualitative properties of this free boundary. In some cases it may have some vertical shape (linking the free boundaries of two stationary solutions), and, under the assumption of a strong absorption, it may have several periodic connected components.